Sociodemographic characterization of the studied Chinese ethnic-racial group in Costa Rica according to the X National Population Census and the VI Housing Census , 2011 - Chen, Susan (2017)
This paper is based on data from the X National Population Census and the VI Housing Census of 2011. We characterize the population considered to belong to the Chinese ethnic-racial group in order to know its socio-demographic profile and its location in the country. We begin with a brief overview of the history of Chinese immigration, which is the predominant racial group within the overall Chinese ethnic-racial group, then we go into the details regarding the general population of Costa Rica considered to belong to this ethnic racial group. Our findings show that this population is relatively young with good education and socioeconomic level that are adequate to afford its members a decent standard of living.  There is, however, a small subgroup of people within this population with at least one unmet basic need.